C Program Verification: VC Explanation and the Standard Library - A. V. Promsky (Моделирование и анализ информационных систем)
The C program verification project is being developed in IIS. Its latest extension is twofold. First, the labeled variant of axiomatic semantics of the C-kernel language was proposed. The labels, introduced in the calculus, correspond to various concepts inherent in verification conditions (VC). These labels can be extracted from terms and rendered into explanations written in the natural language. User-friendly explanations can play a crucial role in VC understanding and error localization. Second, a subset of the C standard library was specified. The specifications written in ACSL correspond to the C-light memory model. The examples in the paper illustrate the use of these two techniques.